The benefits of breathing exercises - Kakorin A. V. (Health saving measures at an educational institution: effective techniques)
This article discusses the most effective breathing exercises for students, as well as their benefits and features of breathing exercises
Keywords: физическое воспитание; дыхательная гимнастика; дыхательные упражнения; physical education; ЛФК; breathing exercises; полное дыхание; локальное дыхание; экономное дыхание; full breath; local breathing; economical breathing